Leave before it's too late: anthropogenic and environmental triggers of autumn migration in a hunted ungulate population. Issue 4 (8th April 2016) - Rivrud, Inger Maren; Bischof, Richard; Meisingset, Erling L.; Zimmermann, Barbara; Loe, Leif Egil; Mysterud, Atle
Abstract: Autumn has to a large extent been neglected in the climate effect literature, yet autumn events, e.g., plant senescence and animal migration, affect fitness of animals differently than spring events. Understanding how variables including plant phenology influence timing of autumn migrations is important to gain a comprehensive understanding of the full annual cycle of migratory species. Here we use 13 yr of data from 60 male and 168 female red deer ( Cervus elaphus ) to identify triggers of autumn migration. We relate the timing of autumn migration to environmental variables like snow fall, temperature, and plant phenology (NDVI), and to onset of hunting, sex, and migration distance. Severe weather has been suggested as the main trigger of autumn migration, but we found that the majority of the individuals had left the summer range well before snow fall (80.3%) and frost (70.5%), and also before the peak deterioration in forage quality (71.9%). Declining temperatures were associated with a higher daily migration potential. Onset of hunting showed the largest effect on migration potential, with a marked increase during the first days of hunting. Individuals still present in the summer range when snow fall, frost, or peak forage deterioration occurred showed a significantly higher migration potential around these events. Males were less responsive to environmental cues, suggesting rutting activity, starting earlier in males, initiate movement prior to such conditions. Also, individuals with longer migration distances had a higher migration potential late in the season than individuals with shorter migration distances. Our study shows that factors beyond weather and plant phenology, such as onset of hunting, may be important triggers of autumn migration. Severe weather and forage deterioration were important triggers for the individuals experiencing this, which suggests a hierarchical response to environmental cues. The trade‐off between staying longer in the summer range and increased energy expenditures if surprised by severe weather is asymmetric, and leaving well in advance can be seen as a risk‐averse tactic.